Hemolytic Anemia due to Glucose 6 Phosphate Dehydrogenase Deficiency Triggered by Type 1 Diabetes Mellitus - Burçe Orman; Semra Çetinkaya; Nergiz Öner; Meltem Akçaboy; Ali Fettah; Naz Güleray Lafcı; Şenay Savaş Erdeve (Galenos Yayincilik, 2023)
Glucose 6 phosphate dehydrogenase (G6PD) is expressed in all tissues and is necessary to maintain oxidant stress capacity of cells. G6PD deficiency is the most common enzymopathy in humans and is among the important causes of hemolytic anemia. It has been reported that severe hemolytic anemia due to G6PD deficiency may develop in newly diagnosed diabetes, especially during the correction of hyperglycemia. To date, nine cases have been published. Genetic analysis was not performed for G6PD deficiency in these published patients. We present a case of hemolytic anemia due to G6PD deficiency secondary to newly diagnosed type 1 diabetes mellitus. Genetic testing was performed for the index patient and revealed a previously reported missense pathogenic variant (c.653C>T; p.Ser218Phe) in the G6PD gene.